Kinetics and Mechanism of Oxidation of Aromatic Aldehydes by Imidazolium Dichromate in Aqueous Acetic Acid Medium - S. Sheik Mansoor; S. Syed Shafi (E-Journal of Chemistry)
The kinetics of oxidation of benzaldehyde (BA) and para-substituted benzaldehydes by imidazolium dichromate (IDC) has been studied in aqueous acetic acid medium in the presence of perchloric acid. The reaction is first order each in [IDC], [Substrate] and [H+]. The reaction rates have been determined at different temperatures and the activation parameters calculated. Electron withdrawing substituents are found to increase the reaction and electron releasing substituents are found to retard the rate of the reaction and the rate data obey the Hammett relationship. The products of the oxidation are the corresponding acids. The rate decreases with the increase in the water content of the medium. A suitable mechanism is proposed.